- 20 Feb '07 22:47 / 1 editThe quadratic formula suggests 2 solutions.

(-t - sqrt( t*t - 4*x*z)) / (2* x)

(-t + sqrt( t*t - 4*x*z)) / (2* x)

Derived by making a perfect square in order to remove the square function

x*y*y + t*y + z = 0

y*y + t*y/x + z/x = 0

y*y + t*y/x = -z/x

y*y + t*y/x + t*t/(4*x*x) = t*t/(4*x*x) - z/x

(y + t/(2*x))^2 = t*t/(4*x*x) - z/x

y + t/(2*x) = +- sqrt(t*t/(4*x*x) - z/x)

y + t/(2*x) = +- sqrt((t*t - 4*x*z)/(4*x*x))

y + t/(2*x) = 1/(2*x)*+- sqrt(t*t - 4*x*z)

y= -t/(2*x) +- sqrt(t*t - 4*x*z)/(2*x)

y= (-t +- sqrt(t*t - 4*x*z))/(2*x) - 21 Feb '07 01:09

i don't even know who you are or where your from but i cn tell from your above post that you really really need to get out more and that your single*Originally posted by geepamoogle***The quadratic formula suggests 2 solutions.**

(-t - sqrt( t*t - 4*x*z)) / (2* x)

(-t + sqrt( t*t - 4*x*z)) / (2* x)

Derived by making a perfect square in order to remove the square function

x*y*y + t*y + z = 0

y*y + t*y/x + z/x = 0

y*y + t*y/x = -z/x

y*y + t*y/x + t*t/(4*x*x) = t*t/(4*x*x) - z/x

(y + t/(2*x))^2 = t*t/(4*x*x) - z/x

y + t/(2*x ...[text shortened]... +- sqrt(t*t - 4*x*z)

y= -t/(2*x) +- sqrt(t*t - 4*x*z)/(2*x)

y= (-t +- sqrt(t*t - 4*x*z))/(2*x)